Growth variation of an ambrosia fungus on different tree species indicates host specialization - Decker, Marcel Hugo; Biedermann, Peter H. W.; van de Peppel, Lennart J. J.; Nuotclà, Jon Andreja (Frontiers in Insect Science, 2025)
Ambrosia beetles rely on mutualistic fungi as a food source for themselves and especially for their offspring, yet the influence of host tree species on fungal growth and specialization remains poorly understood. In this study, we investigated the growth performance of the ambrosia fungus Dryadomyces montetyi, an important nutritional symbiont of the oak pinhole borer Platypus cylindrus, on semi-artificial media infused with extracts of four tree species: Quercus robur, Fagus sylvatica, Abies alba, and Pseudotsuga menziesii. Fungal growth was quantified over time using logistic models of the growth area and final dry weight measurements. The growth of D. montetyi differed significantly among the different host tree substrates. Growth on F. sylvatica was comparable to that on Q. robur; however, both conifer-derived media (A. alba and P. menziesii) exhibited significantly reduced surface expansion speed. Interestingly, growth speed on the European native A. alba was measurably higher than on the non-native P. menziesii. Q. robur medium had the highest fungal density of all tree hosts. However, density estimates were close and only nutrient-rich laboratory growth medium without tree extract differed significantly, as it had by far the highest density as well as growth speed of all measured media. Our findings show that fungal performance reflects the known preference of P. cylindrus for deciduous host trees. Host-related specialization of the fungal symbiont certainly determines host tree selection by P. cylindrus, which affects the evolution of the tripartite interactions between beetle, fungus and host trees.